Targeted Delivery of Mesenchymal Stem Cell-Derived Bioinspired Exosome-Mimetic Nanovesicles with Platelet Membrane Fusion for Atherosclerotic Treatment - Jiang Y; Yu M; Song ZF; Wei ZY; Huang J; Qian HY (International Journal of Nanomedicine, 2024)
Yu Jiang,1,* Miao Yu,1,* Zhi-Feng Song,1,* Zhi-Yao Wei,1 Ji Huang,2 Hai-Yan Qian1 1Center for Coronary Heart Disease, Department of Cardiology, Fu Wai Hospital, National Center for Cardiovascular Diseases of China, State Key Laboratory of Cardiovascular Disease, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 2Center for Coronary Artery Disease, Division of Cardiology, Beijing Anzhen Hospital, Capital Medical University, Beijing Institute of Heart, Lung, and Blood Vessel Diseases, National Clinical Research Center for Cardiovascular Diseases, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ji Huang, Center for Coronary Artery Disease, Division of Cardiology, Beijing Anzhen Hospital, Capital Medical University, Beijing Institute of Heart, Lung, and Blood Vessel Diseases, National Clinical Research Center for Cardiovascular Diseases, Beijing, 100029, People’s Republic of China, Email drjihuang@163.com Hai-Yan Qian, Center for Coronary Heart Disease, Department of Cardiology, Fu Wai Hospital, National Center for Cardiovascular Diseases of China, State Key Laboratory of Cardiovascular Disease, Chinese Academy of Medical Sciences and Peking Union Medical College, 167 Beilishi Road, Beijing, 100037, People’s Republic of China, Email ahqhy712@163.comPurpose: Accumulating evidence indicates that mesenchymal stem cells (MSCs)-derived exosomes hold significant potential for the treatment of atherosclerosis. However, large-scale production and organ-specific targeting of exosomes are still challenges for further clinical applications. This study aims to explore the targeted efficiency and therapeutic potential of biomimetic platelet membrane-coated exosome-mimetic nanovesicles (P-ENVs) in atherosclerosis.Methods: To produce exosome-mimetic nanovesicles (ENVs), MSCs were successively extruded through polycarbonate porous membranes. P-ENVs were engineered by fusing MSC-derived ENVs with platelet membranes and characterized using transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), and Western blot. The stability and safety of P-ENVs were also assessed. The targeted efficacy of P-ENVs was evaluated using an in vivo imaging system (IVIS) spectrum imaging system and immunofluorescence. Histological analyses, Oil Red O (ORO) staining, and Western blot were used to investigate the anti-atherosclerotic effectiveness of P-ENVs.Results: Both ENVs and P-ENVs exhibited similar characteristics to exosomes. Subsequent miRNA sequencing of P-ENVs revealed their potential to mitigate atherosclerosis by influencing biological processes related to cholesterol metabolism. In an ApoE−/− mice model, the intravenous administration of P-ENVs exhibited enhanced targeting of atherosclerotic plaques, resulting in a significant reduction in lipid deposition and necrotic core area. Our in vitro experiments showed that P-ENVs promoted cholesterol efflux and reduced total cholesterol content in foam cells. Further analysis revealed that P-ENVs attenuated intracellular cholesterol accumulation by upregulating the expression of the critical cholesterol transporters ABCA1 and ABCG1.Conclusion: This study highlighted the potential of P-ENVs as a novel nano-drug delivery platform for enhancing drug delivery efficiency while concurrently mitigating adverse reactions in atherosclerotic therapy.Keywords: exosome-mimetic nanovesicles, platelet membrane-coated nanovesicles, biomimicry, targeted delivery, atherosclerosis